Challenges and Practices of Implementing Inclusive Education: A Review of Teachers’ Classrooms Preparation and Parental Support - Chandra Acharja, Dijendra; Begum, Shamima (South Asian Journal of Social Sciences and Humanities, 2025)
In Bangladesh, inclusive education is underscored in the Constitution, the National Education Policy 2010, and the SDGs; however, in practice, this is not without challenges. There are not enough trained teachers; classes are too large, and resources are too scarce. Attitudes towards linguistic disabilities and marginal communities remain negative; weak school leadership and teacher reluctance all conspire against their success. Parent engagement is still minimal because of poverty, stigma, and ignorance. Interference in policy making, as well as politicization, exacerbates the policy–practice gap. This study examines the reasons behind the failure of inclusive education in Bangladesh, with a particular emphasis on the classroom experiences of teachers and the level of parental involvement in the learning process. This research further argues that to achieve inclusion, the cooperative relationship between parents and teachers should be strengthened, teachers’ competence should be enhanced, classroom practices should be applied consistently, and long-term plans should be made for marginalized children.